Negative pressure wound therapy in grade 1 and 2 diabetic foot ulcers: A randomized controlled study. Issue 1 (January 2021) - Maranna, Haraesh; Lal, Pawan; Mishra, Anurag; Bains, Lovenish; Sawant, Gaurish; Bhatia, Rahul; Kumar, Pritesh; Beg, Mohd Yasir
Abstract: Background and aims: Foot ulcers are one of the major causes of morbidity and mortality among diabetics in India. Early diagnosis and timely management is vital in preventing the progression of the disease which may require amputation. Conventional methods take a long time for healing. This study aims to compare negative pressure wound therapy (NPWT) and conventional saline dressings in diabetic foot ulcer (DFU) healing. Methods: This prospective randomized study was conducted in 45 patients with grade 1 and 2 DFUs. 22 patients in group A received NPWT and 23 patients in group B received saline dressings. The formation of granulation tissue, reduction in ulcer size, duration of hospital stay and time for complete healing of wounds were assessed. Results: The formation of granulation tissue (91.14 vs 52.61%, p < 0.001) and reduction in ulcer size (40.78 vs 21.18%, p = 0.008) at 14 days was significantly more in group A. The duration of hospital stay (15.68 vs 29.00 days, p < 0.001) and time for 100% coverage of the wound with granulation tissue (14.82 ± 7.30 vs 44.57 ± 7.11 days, p < 0.001) was significantly less in group A. Complete healing of wounds at 3 months was observed in 20 patients (90.9%) in group A and 6 patients (26.1%) in group B (p = 0.006). Conclusion: In our study NPWT led to early reduction in ulcer size, more granulation tissue formation, shorter hospital stay and complete wound healing. In lower and middle income countries like India with high prevalence of DFUs, early recovery is a boon to the patients to resume their daily activities. Highlights: Diabetic foot ulcers are one of the major causes of mortality and morbidity among the 62 million diabetics in India. Patients were prospectively randomized to receive either 14 days of NPWT or saline dressings and followed up for 3 months. Our study highlights that the formation of granulation tissue and reduction in ulcer size is significantly more with NPWT. The duration of stay and complete healing of wound was significantly more with NPWT and may prevent progression of disease.